Crisis de seguridad y el Estado constitucional. Debate sobre el incremento de penas - Armijos Reyes, Vagner Armando (2023)
The crisis of insecurity that Ecuador is going through, has turned into a problem that is constantly haunting all its provinces. This problem has arisen due to the increase in crime related to organized crime and from which, other types of crimes such as hired killings, violent robbery, the sale of illegal substances, the collection of illegal taxes from commercial premises called “vaccines”, among others, have emerged; as a result of all these crimes, the politicians from the government have been forced to seek an immediate solution to try to resist this crisis of insecurity, taking refuge under the most repressive part of the State, which is the punitive power; however, the application of this type of punishment violates what is stated in the Ecuadorian Constitution, which establishes a criminal law supposedly to prevent crime and to rehabilitate behaviours that transgress and violate the law. This paper analyses the problem of insecurity within the society, and delves into the role played by the government based on the Constitution. An analysis of the feasibility of increasing the penalties associated with crimes is proposed, also the fundamental concepts related to the Constitutional State of Rights are examined, and its attributes and its function are detailed. In addition, some arguments are provided to support the idea that the exclusive use of the government’s punitive power to combat crime goes against the principles that govern the current Constitutional State focusing on individual and collective rights. In performing the planned process, it is concluded that the increase in penalties violates the rights of the Ecuadorian Constitution by not reducing the imprisonment rate, preventing criminal acts or reducing the crime rate at the national level. Therefore, it is not an effective solution in the fight against crime and the security crisis, nor does it consider rehabilitation as an alternative, opting instead for offensive measures against crime.